2012
DOI: 10.1590/s1679-45082012000100015
|View full text |Cite
|
Sign up to set email alerts
|

Interventions performed by the clinical pharmacist in the emergency department

Abstract: 13%); compatibility: 50 (4%); dilution: 121 (9.77%); legibility: 39 (3.15%); pharmacovigilance: 7 (0.56%); adverse reaction to medications: 7 (0.56%); allergy: 35 (2.82%); infusion time: 76 (6.13%); indication: 52 (4.20%); medication reconciliation: 2 (0.16%); enteral medication administration: 38 (3%); scheduling: 7 (0.56%); specific anticoagulant protocol: 44 (3.55%); specific hypoglycemic agent protocol: 42 (3.99%). Conclusion: The study allowed the demonstration of the importance of the clinical pharmacist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 12 publications
0
23
0
12
Order By: Relevance
“…Other authors have pointed out this aspect (Vira et al, 2006;Lubowski et al, 2007;Cobaugh et al,2008;Pippins et al, 2008;Coffey et al, 2009;Stone et al, 2010;Miranda et al, 2012;Chhabra et al, 2012;Haynes et al, 2012).…”
Section: Identified Problem Interventionmentioning
confidence: 95%
See 1 more Smart Citation
“…Other authors have pointed out this aspect (Vira et al, 2006;Lubowski et al, 2007;Cobaugh et al,2008;Pippins et al, 2008;Coffey et al, 2009;Stone et al, 2010;Miranda et al, 2012;Chhabra et al, 2012;Haynes et al, 2012).…”
Section: Identified Problem Interventionmentioning
confidence: 95%
“…It has been shown that pharmacists can contribute in improving the quality and safety of medication use during in patients' care, through medication reconciliation strategies (Vira et al, 2006;Lubowski et al, 2007;Cobaugh et al,2008;Pippins et al, 2008;Coffey et al, 2009;Stone et al, 2010;Miranda et al, 2012;Chhabra et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is suggested that the participation of the clinical pharmacist in the care teams would contribute to the quality of patient care and safety regarding drug therapy, assisting in the identification and prevention of prescription and medication administration errors, besides guiding the teams on the possible modifications of solid medicines (23) .…”
Section: Discussionmentioning
confidence: 99%
“…Em relação aos erros de medicação envolvendo o uso de diluente inadequado, foi obtido um índice igual a 16%, superior ao encontrado em um estudo (9,77%) (20), e inferior ao descrito por outro estudo (67,85%) (21). Contudo, tal fato pode ser justificado pelas diferentes abordagens metodológicas adotadas nestes estudos.…”
Section: Elaboração Do Materials Didático-instrucionalunclassified
“…O erro envolvendo a infusão em Y de medicamento incompatível configura um erro de administração medicamentosa, e correspondeu a 32% dos erros observados neste estudo (25). Este resultado corrobora com outros estudos (1,2,3,11,20,24) e está relacionado aos esquemas terapêuticos envolvendo a prescrição simultânea de múltiplos fármacos intravenosos, às falhas na comunicação entre a equipe de farmácia e a equipe assistencial em fornecer suporte nas questões relacionadas à compatibilidade dos medicamentos; à falha no planejamento assistencial de enfermagem relacionada ao aprazamento de vários fármacos intravenosos; e à necessidade de associar diferentes medicamentos numa única via sem que esta esteja pautada em fundamentos teóricos consistentes.…”
Section: Elaboração Do Materials Didático-instrucionalunclassified